Association Between Hormonal Birth Control, Substance Use, and Depression - Newman, Sharlene D. (Frontiers in Psychiatry, 2022)
Objective: The current study examined the impact of the use of hormonal birth control, cannabis and alcohol on depression symptoms. Study Design: Survey data from 3320 college-aged women collected over a two year period was examined. Depression symptoms were assessed using the PHQ-9. Results: Individuals taking hormonal birth control (N=996; age = 19.1±1.6 years) had lower overall depression scores than did those not taking birth control (N=2324; age = 19.1±1.8 years) with15.2% of those not taking hormonal birth control had depressive symptoms while 12.1% of those in the birth control group had depressive symptoms. Additionally, those taking hormonal birth control had higher scores on the alcohol and cannabis use assessment. A between-subjects ANOVA with depression score as the dependent variable found significant effects hormonal birth control use, cannabis and alcohol use, as well as a significant interaction between cannabis use and hormonal birth control use. Conclusions: While there are some limitations (e.g., the between subjects design makes it such that there may be uncontrolled differences between groups), the results suggest that eliminating the cycling of hormones may help to reduce depressive symptoms. Implications: More studies examining the impact of hormonal birth control and substance use on depression are required. The results suggest a potential interaction between cannabis and hormonal birth control use on depression symptoms that is not observed for alcohol which implies that alcohol and cannabis are related to depression via different mechanisms.